2023
DOI: 10.3390/pharmaceutics15030748
|View full text |Cite
|
Sign up to set email alerts
|

Application of Amniotic Membrane in Skin Regeneration

Abstract: Amniotic membrane (AM) is an avascular structure composed of three different layers, which contain collagen, extracellular matrix, and biologically active cells (stem cells). Collagen, a naturally occurring matrix polymer, provides the structural matrix/strength of the amniotic membrane. Tissue remodeling is regulated by growth factors, cytokines, chemokines, and other regulatory molecules produced by endogenous cells within AM. Therefore, AM is considered an attractive skin-regenerating agent. This review dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…( Ohno et al, 1983 ; Liu et al, 2019 ; Shariatzadeh et al, 2021 ). The basement membrane of AM also contains collagen (type III, IV, and V) and various non-collagenous glycoproteins, such as elastin, laminin, nidogen, fibronectin, and vitronectin as well as glycosaminoglycans like hyaluronic acid ( Arki et al, 2023 ; Fitriani et al, 2023 ). The stromal layer is composed of three sublayers, including 1) compact layer, 2) fibroblast layer, and 3) intermediate layer ( Dadkhah Tehrani et al, 2021 ).…”
Section: Structural and Biochemical Features Of Amnionmentioning
confidence: 99%
“…( Ohno et al, 1983 ; Liu et al, 2019 ; Shariatzadeh et al, 2021 ). The basement membrane of AM also contains collagen (type III, IV, and V) and various non-collagenous glycoproteins, such as elastin, laminin, nidogen, fibronectin, and vitronectin as well as glycosaminoglycans like hyaluronic acid ( Arki et al, 2023 ; Fitriani et al, 2023 ). The stromal layer is composed of three sublayers, including 1) compact layer, 2) fibroblast layer, and 3) intermediate layer ( Dadkhah Tehrani et al, 2021 ).…”
Section: Structural and Biochemical Features Of Amnionmentioning
confidence: 99%
“…Amniotic membrane stem cells (AMSCs), adipose-derived stem cells (ADSCs), and human umbilical cord mesenchymal stem cells (hUC-MSCs) are all being explored for their potential in skin rejuvenation due to their regenerative properties [ 81 ]. AMSCs are multipotent with low immunogenicity and can be easily obtained from the placenta, avoiding ethical issues associated with embryonic stem cells [ 82 ]. Their anti-aging potential has been associated with the release of growth factors, angio-modulatory cytokines, anti-bacterial peptides, and anti-inflammatory molecules [ 82 ].…”
Section: Reviewmentioning
confidence: 99%
“…AMSCs are multipotent with low immunogenicity and can be easily obtained from the placenta, avoiding ethical issues associated with embryonic stem cells [ 82 ]. Their anti-aging potential has been associated with the release of growth factors, angio-modulatory cytokines, anti-bacterial peptides, and anti-inflammatory molecules [ 82 ]. A study showed that a topical application of AMSC metabolic products combined with vitamin E significantly improved wrinkles, ultraviolet spots, and pores in patients with photoaging [ 83 ].…”
Section: Reviewmentioning
confidence: 99%
“…Therefore, the selection of an appropriate amniotic tissue processing method is crucial in order to preserve tissue quality, maintain tissue integrity, and retain the inherent biological properties. Amniotic tissues possess unique biological properties that make them effective in promoting the healing process of ulcers caused by various factors, including burns, diabetes, neuropathy, and bedsores [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its aforementioned benefits, HAM possesses various other properties, including antifibrotic, anti-inflammatory, angiogenic, bacteriostatic, and thrombolytic properties. Furthermore, studies have documented that HAM transfers induce changes in thick-walled vessels, resulting in a reversion towards normal vasculature characterized by vessel wall thinning and widening of the lumen [ 6 ].…”
Section: Introductionmentioning
confidence: 99%